Vaccine hesitancy for coronavirus SARS-CoV-2 in Varanasi India - Srivastava, Utkarsh; Tripathi, Avanish Kumar; Kaur, Jagjeet; Devi, Sabita; Verma, Shipra; Singh, Vanya; Das, Debashruti; Singh, Prajjval Pratap; Mishra, Rahul Kumar; Kumar, Nikhil A.; Mishra, Vijaya Nath; Kumar, Pradeep; et al. (Frontiers in Public Health, 2022)
With the rollout of the world's largest vaccine drive for SARS-CoV-2 by the Government of India on January 16 2021, India had targeted to vaccinate its entire population by the end of 2021. Struggling with vaccine procurement and production earlier, India overcome these hurdles, but the Indian population still did not seem to be mobilizing swiftly toward vaccination centers. The severe second wave has slowed the vaccination pace and was also one of the major contributing factors to vaccine hesitancy. To understand the nature of vaccine hesitancy and its underlying factors, we conducted extensive online and offline surveys in Varanasi and adjoining regions using structured questions. Most respondents were students (0.633). However, respondents from other occupations, such as government officials (0.10), have also participated in the study. Interestingly, most people (0.75) relied on fake news and did not take COVID-19 seriously. Most importantly, we noticed that a substantial proportion of respondents (relative frequency 0.151; mean age 24.8 years) reported that they were still not interested in vaccination. We observed a significant association between vaccine hesitancy and socioeconomic status (χ2 = 307.6, p < 0.001). However, we failed to detect any association between vaccine hesitancy and gender (χ2 = 0.007, p > 0.5). People who have neither been vaccinated nor have ever been infected may become the medium for spreading the virus and creating new variants, which may lead to the vaccine-resistant variant. We expect this extensive survey to help the Government upgrade their vaccination policies for COVID-19 in North India.